Utility of Non-EPI DWI MRI in the Management of Pediatric Cholesteatoma - T.M, Sreenivasa Murthy; Nagadi, Anita; Mohan, Sneha Krishna (Annals of Otology and Neurotology, 2019)
Introduction Cholesteatoma in children can be acquired or congenital and is generally extensive. The most commonly used technique for the removal of cholesteatoma is intact canal wall mastoidectomy. This invariably leads to second-look surgery to assess for recurrence or residual cholesteatoma. Magnetic resonance imaging (MRI) with non–echo-planar imaging (non-EPI) diffusion-weighted imaging (DWI) is an accurate noninvasive imaging option that can be used in diagnosing primary cholesteatoma. This can also be used to diagnose residual or recurrent cholesteatoma in patients who have undergone intact canal wall mastoidectomy.Case Report A 7-year-old male patient presented with a 1-week history of foul-smelling discharge from the right ear. On examination, a polypoidal mass with keratinized debris was seen. A diagnosis of cholesteatoma of right ear was made. Imaging with high-resolution computed tomography (HRCT) of the temporal bone and non-EPI DWI MRI confirmed the same. The child underwent an intact canal wall mastoidectomy and was followed up at 2 years with non-EPI DWI MRI to monitor any residual or recurrent cholesteatoma.Conclusion Non-EPI DWI MRI provides a convenient, accurate, and noninvasive method of evaluating and monitoring for residual or recurrent cholesteatoma and thus helps avoid unnecessary second-look surgery.
Keywords: non-EPI DWI MRI; high-resolution computed tomography; relook surgery